Penyelesaian Kredit Bermasalah Dengan Jaminan Fidusia Antara Nasabah Dengan Perusahaan Pembiayaan - Alethea Suryana, Salsabila (Universitas Jambi, Fakultas Hukum, 2024)
The purpose of the research is to determine the occurrence of problem loans between customers and companies and to determine the role of the parties in resolving problem loans with guaranteed fiduciary rights between customers and the financing company PT. Saic General Motors Wuling Multifinance Indonesia Jambi Branch. The research method used is empirical juridical. Based on the research results, it was found that the cause of credit problems between customers and the financing company PT. Saic General Motors Wuling Multifinance Indonesia Jambi Branch, namely the inability of customers to continue credit payments, the death of creditors, a decline in creditors' economic conditions, creditors suddenly losing their source of livelihood, and problems with credit assessment by debtors. The role of PT. Saic General Motors Wuling Multifinance Indonesia Jambi Branch in resolving problem loans with fiduciary guarantees with customers is by carrying out credit collection based on the terms of the agreement and applicable law. The initial steps taken are to communicate and remind customers by telephone 3 (three) days before the due date, provide 1 (one) warning letter (SP) to 3 (three) warning letters (SP), and negotiate by offering restructuring credit. If all these efforts are not heeded and the customer is not cooperative, then fiduciary guarantees will be executed involving third parties in the form of external collector services and the police. If the customer shows significant resistance and uncooperative behavior, then PT. Saic General Motors Wuling Multifinance Indonesia Jambi Branch will take legal action.